ANALYSIS OF RELATIONSHIP BETWEEN MORAL MATURITY AND HUMAN VALUES OF UNIVERSITY STUDENTS - Tatık, Ramazan Şamil; Akan, Yunus (My University, 2021)
The aim of this study was to reveal the relationship between the moral maturity and human values of university students. The study was a quantitative research and was conducted with the correlational survey model. The study group of the study consisted of 764 students selected by simple random sampling method, one of the random sampling methods from five academic units (one college, one vocational high school and three faculties) among the students who continued their education in the 2019-2020 academic year at a state university. A data collection tool consisting of "Moral Maturity Scale" and "Human Values Scale" was used. Independent Samples t-Test, ANOVA and Pearson Product Moment Correlation Coefficient statistical techniques were used to analyze the data. According to the results of the study, it was found that there was a significant difference in university students ' moral maturity levels in terms of gender, academic unit, father's level of education, mother's level of education, economic status and the number of books they read in the last month. Furthermore, it was found that there was a significant difference in the human values of university students depending on gender, academic unit and the number of books they read in the last month. It was revealed that there was a positive, strong and significant relationship between moral maturity and human values scores of university students. As a result, moral maturity and human values differed according to various variables, and there was a high relationship between the two concepts mentioned.